Development of a soccer ball launching device - Mohd Hasnun Arif, Hassan; Zahari, Taha; Mohd Ali Hanafiah, Shaharudin; Lim, Kok Wee; Zulfika, Anuar (Springer Singapore, 2018)
Soccer players are allowed to use their heads to direct the ball to the teammates during the game. Studies have shown that purposeful heading of the ball in soccer might cause long-term traumatic brain injury. In order to analyze the impact of soccer heading on the brain in the laboratory, a device that can launch the ball at constant speed is required. This project aims to develop a device, which can launch the ball towards a target such as an instrumented dummy headform at desired speeds. Two counter-rotating wheels that are rotated by two AC motors were used as the launching mechanism. The use of AC motors is economical, but their speeds cannot be easily controlled. Thus, a release mechanism that automates the switching of the motor as well as feeding the ball was developed. Testing shows that the device is capable of launching the ball up to a maximum speed of 18Â m/s. This corresponds to the reported maximum heading speed in soccer. The use of the release mechanism allows the ball speed to be varied. A soccer ball launching device was successfully developed. The device is not only economical, but also capable of launching the ball at desired speeds.